Improving of in vitro Biodegradation Resistance in a Chitosan Coated Magnesium Bio-composite. Issue 8 (August 2015) - Liangjian, Chen; Jun, Zhao; Kun, Yu; Chang, Chen; Yilong, Dai; Xueyan, Qiao; Zhiming, Yu
Abstract: A magnesium base composite with a chitosan coating was prepared to study its in vitro degradation behavior in simulated body fluid. The in vitro test results show that the immersion corrosion rate, the pH values of the simulated body fluids and the released metal ion concentration of the chitosan coated composite are all lower than those of the uncoated magnesium composite. The in vitro cytotoxicity test indicates that the chitosan coated specimen is safe for cellular applications with a toxic grade of zero. The chitosan coating is an effective corrosion resistant layer that reduces the hydrogen release of the implant composite, thereby decreasing the damage of the corrosion products of magnesium composite as an implant material.